The neurons expressing calcium-binding proteins in the amygdala of the guinea pig: precisely designed interface for sex hormones - Równiak, Maciej (Brain Structure and Function, 2017)
The generation of emotional responses by the amygdala is determined largely by the balance of excitatory and inhibitory inputs to its principal neurons. These responses are often sex-specific, and any imbalance in excitatory and/or inhibitory tones leads to serious psychiatric disorders which occur with different rates in men versus women. To investigate the neural basis of sex-specific processing in the amygdala, relationships between the neurons expressing calbindin (CB), parvalbumin (PV) and calretinin (CR), which form in the amygdala main subsets of γ-aminobutyric acid (GABA)-ergic inhibitory system, and neurons endowed with oestrogen alpha (ERα), oestrogen beta (ERβ) or androgen (AR) receptors were analysed using double immunohistochemistry in male and female guinea pig subjects. The results show that in various nuclei of the amygdala in both sexes small subsets of CB neurons and substantial proportions of PV neurons co-express ERβ, while many of the CR neurons co-express ERα. Both these oestrogen-sensitive populations are strictly separated as CB and PV neurons almost never co-express ERα, while CR cells are usually devoid of ERβ. In addition, in the medial nucleus and some other neighbouring regions, there are non-overlapping subpopulations of CB and CR neurons which co-express AR. In conclusion, the localization of ERα, ERβ or AR within subsets of GABAergic interneurons across diverse amygdaloid regions suggests that steroid hormones may exert a significant influence over local neuronal activity by directly modulating inhibitory tone. The control of inhibitory tone may be one of the mechanisms whereby oestrogen and androgen could modulate amygdala processing in a sex-specific manner. Another mechanism may be thorough steroid-sensitive projection neurons, which are most probably located in the medial and central nuclei.